Performance und Praxis: Praxeologische Erkundungen in Tanz, Theater, Sport und Alltag - Klein, Gabriele; Göbel, Hanna Katharina (transcript, 2017)
»Praxis« has been a central concept in art and art theory for a long time, and it has taken on a new shade in the context of contemporary performative art forms and process-oriented working methods and artistic research. At the same time, with the practical turn, »praxis« has become a central object of research, and the practical-theoretical has become an important approach and process in the social sciences and cultural studies. This interdisciplinary volume brings together contributions which empirically and theoretically deal with the concept and methodological approach of »praxis« at the intersections of the performing arts and everyday life. Four topics stand at the center of this: the in/stability of praxis, affectivity and praxis, aesthetics and praxis, as well as praxis and the political.